Willingness to take action toward climate change in Agriculture Experts in Khuzestan Province. - Masoud Yazdanpanah; Tahereh Zobeidi; Hajar Zaery (تحقیقات کاربردی علوم جغرافیایی)
Greenhouse emissions from agricultural as a consequence of human activities are causing climate change. Small changes in agricultural practices have a large potential for reducing greenhouse gas emissions. Intention of Agriculture Experts in order to mitigation climate change Can play an important role in finding appropriate solutions for each region in climate change mitigation and deliver them to their farmers. However Intentions to take mitigation actions are, most likely, influenced by a range of factors. The purpose of this study was to investigate of factors influencing on Agriculture Experts in order to mitigation greenhouse gases. This research in terms of purpose is an applied research and in terms of methodology is survey research. The statistical population of this research consisted of 520 Agriculture Experts in Khuzestan Province. A sample of 320 persons was selected through Random Stratified Sampling method. The survey instrument was a questionnaire which its validity confirmed by experts. The reliability of the questionnaire using Cronbach's alpha coefficient (α= 0/67-0/87) has been approved. Our analysis reveal, direct experience were predictors of risk perception, self-efficacy and environmental attitude. The changes in self-efficacy and environmental attitude were also strong predictors of changes in intention.  The variables of self-efficacy and environmental attitude could predict 61 percent of variations in willingness to mitigating climate change. Therefore experience indirectly affected on the mitigation intention. Lastly we provide recommendations on how these findings can be used to climate change mitigation.